The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1051/kmae/2018025
|View full text |Cite
|
Sign up to set email alerts
|

Municipal wastewater can result in a dramatic decline in freshwater fishes: a lesson from a developing country

Abstract: Impacts of ineffective wastewater management on the biodiversity of receiving waters in developing countries are poorly documented. Using a before-after-control-impact methodology, we measured the effects of untreated wastewater release on the fish community in the Barnoi River, Bangladesh. In 2006, prior to untreated wastewater discharge, fish abundance, species richness and water quality were similar across sampling sites. In 2016, after 8 years of wastewater release to the downstream reach, fish abundance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…Also, the fast flowing nature of streams lowers the efficiency of catching the prawn species. A similar reason was reported by Galib et al (2018) in the case of reduced fish abundance during this season. Akhi et al (2020) reported that fast flow of water reduces the availability of food making the conditions unfavorable.…”
Section: Variation In Abundance Of Prawn Speciessupporting
confidence: 87%
“…Also, the fast flowing nature of streams lowers the efficiency of catching the prawn species. A similar reason was reported by Galib et al (2018) in the case of reduced fish abundance during this season. Akhi et al (2020) reported that fast flow of water reduces the availability of food making the conditions unfavorable.…”
Section: Variation In Abundance Of Prawn Speciessupporting
confidence: 87%
“…We employed a BACI approach in S 1 and S 3 (Boys et al., 2012; Galib et al., 2018; Galib, et al., 2018) and a control–impact approach in S 2 , where sampling years represent time before–after and status of signal crayfish (present or absent) in streams represents control (i.e. uninvaded streams) and impact (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…In S 1 , as both fish and environmental data were available, the multivariate BIOENV procedure, based on Euclidean distances (Clarke & Ainsworth, 1993), was employed to find out the best subset of environmental variables with maximum (rank) correlation (Pearson's) with community dissimilarities (e.g. Boys et al., 2012; Galib, et al., 2018). Along with all the environmental variables (depth, flow velocity, flow typology, DO, temperature, pH, substrate, canopy cover), we also considered density of signal crayfish in the BIOENV model to determine the role of signal crayfish for changes in fish community over time.…”
Section: Methodsmentioning
confidence: 99%
“…The negative impact of forests on transparency highlighted here is hardly compatible with the findings from several publications that instead support a positive effect of forests on water transparency (Kasangaki, Chapman, & Balirwa, 2008 ;Roozen et al, 2003) or report that they reduce turbidity (Brauman, Daily, Duarte, & Mooney, 2007 ;Cunha, Sabogal-Paz, & Dodds, 2016), and is difficult to interpret. The lower transparency values observed in lake villages (LV) with high visitation rates and direct discharge of domestic effluent are more consistent with the expected mechanical effects of these stressors (Galib et al, 2018). Mangroves not only reduce the total nutrient load (Wang, Cheng, Chen, & Kuo, 2021), but they also have the potential to absorb pollutants (Nguyen, Truong, & Pham, 2020) and should therefore lead to a decrease in BOD.…”
Section: Physicochemical Parameters Selected and Impacts Of Stressorsmentioning
confidence: 69%